1985
DOI: 10.1002/j.1460-2075.1985.tb04156.x
|View full text |Cite
|
Sign up to set email alerts
|

All six GC-motifs of the SV40 early upstream element contribute to promoter activity in vivo and in vitro.

Abstract: Recombinants in which the six GC-motifs (I -VI) present in the upstream element of the SV40 early promoter region have been point mutated either individually or in pairs were used to determine the possible contribution of each GC-motif to the function of the overlapping early-early and late-early SV40 promoters. GC-motif I, and to a lesser extent, GC-motifs H and HI, are critical for initiation at the early-early start sites. GC-motifs IV -VI play a subsidiary role. Mutations in GCmotifs I and II do not decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
62
2

Year Published

1985
1985
1992
1992

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 103 publications
(70 citation statements)
references
References 31 publications
6
62
2
Order By: Relevance
“…The upstream elements which interact with the core origin coincide with those previously demonstrated to comprise the early promoter sequences and to bind the transcription factor Spl (2,15). The effect on DNA replication of altering the relative spacing between the mutated core origin and the 21-bp repeated sequences containing the G-C boxes correlates precisely with the effect observed previously on the efficiency of initiation of early transcription in SV40 (37).…”
Section: Discussionsupporting
confidence: 71%
“…The upstream elements which interact with the core origin coincide with those previously demonstrated to comprise the early promoter sequences and to bind the transcription factor Spl (2,15). The effect on DNA replication of altering the relative spacing between the mutated core origin and the 21-bp repeated sequences containing the G-C boxes correlates precisely with the effect observed previously on the efficiency of initiation of early transcription in SV40 (37).…”
Section: Discussionsupporting
confidence: 71%
“…Therefore, it is possible that these effects of box DNA are due to stereospecific alignments of box DNA among factors acting as repressor, enhancer, and promoter and to steric hindrance of box DNA among repressor proteins. It has been reported that the transcription factor Spl, bound to the G-C motif of the SV40 promoter, is aligned on the same side of the helix and may interact with the promoter (5,11,14). The stereospecific alignment of Spl and enhancer factors (30) is required for efficient transcription of SV40 early genes (35).…”
Section: Discussionmentioning
confidence: 99%
“…The TATA box located 25-30 bp upstream from the start site is required for both accurate and efficient in vitro transcription (Corden et al, 1980;Wasylyk et al, 1980;Breathnach and Chambon, 1981;Hu and Manley, 1981;Grosveld et al, 1981;Lee et al, 1982;Wasylyk et al, 1983). Elements located further upstream bp from the start site) are required for maximally efficient in vitro transcription from the promoters of a variety of viral and cellular genes (Tsuda and Suzuki, 1981;Grosschedl and Birnstiel, 1982;Hen et al, 1982;Hansen and Sharp, 1983;Jove and Manley, 1984;Miyamoto et al, 1984; IRL Press Limited, Oxford, England Vigneron et al, 1984;Barrera-Saldana et al, 1985). Stimulation of in vitro transcription by the SV40 enhancer element has also been documented Wildeman et al, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…Stimulation of in vitro transcription by the SV40 enhancer element has also been documented Wildeman et al, 1984). Recent competition and footprinting experiments, using either crude extracts of HeLa cells or partially purified transcription factors, showed that these various promoter elements may be specifically recognized by transcription factors in vitro: (i) the TATA box element appears to bind a general transcription factor (Davison et al, 1983;Parker and Topol, 1984a) in the presence of another general stimulatory transcription factor, 43-kd STF ; (ii) the upstream elements of the SV40 early promoter (2 1-bp repeat region) (Dynan and Tjian, 1983;Gidoni et al, 1984;Barrera-Saldana et al, 1985), the Drosophila heat shock hsp70 gene (Parker and Topol, 1984b) and the adenovirus-2 major late promoter (Ad2MLP) bind specific factors required for efficient in vitro transcription; (iii) the SV40 enhancer element appears to bind specific trans-acting factors (Wildeman et al, 1984Sassone-Corsi et al, 1985).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation